Circulating tumor DNA profile and its clinical significance in patients with hormone receptor-positive and HER2-negative mBC - Tang, Yu; Li, Jing; Liu, Binliang; Ran, Jialu; Hu, Zhe-Yu; Ouyang, Quchang (Frontiers in Endocrinology, 2022)
Background After early-line (first- and second-line) endocrine therapy, hormone-receptor (HR)-positive and/ human epidermal growth factor receptor 2 (HER2)HER2-negative metastatic breast cancers (MBCmBCs) become resistant to endocrine therapy. Genetic alterations may underlie resistance to endocrine therapies. This study aims to investigate the circulating tumor DNA (ctDNA) alterations and the clinical implication in hormone-receptor-positive, HER2-negative metastatic breast cancer patients with multiline endocrine therapy failure. Methods This registered study (NCT05079074, ClinicalTrials.gov) enrolled 104 patients with hormone-receptor-positive, HER2-negative metastatic breast cancer who progressed after the early-line endocrine therapy. ctDNA alterations were analyzed by next generation sequencing (NGS). ctDNA alterations were ranked and clustered by using R ‘ComplexHeatmap’ and ‘hclust’ function. ctDNA-guided therapy was administrated. Progression-free survival (PFS) was assessed COX regression analysis, and Kaplan-Meier curves were plotted. Findings The top ctDNA altered genes were TP53 (39%), PIK3CA (38%), BRCA1/2 (13%), ESR1 (12%), FGFR (11%), ERBB2 (11%), and GATA3 (9%). Among these genes, TP53, PIK3CA helix domain mutation (PIK3CA-HD), FGFR, ESR1 and GATA3 were important related to endocrine therapy -resistancet genes. The genetic landscapes changed and tumor mutation burden increased in both TP53-altered and PIK3CA-altered patients. Both BRCA1/2 and ERBB2 alterations correlated with TP53 alterations (P=0.02 and P=0.04, respectively). However, while 93% BRCA1/2 alterations concentrated in PIK3CA-wildtype patients, 82% ERBB2 alterations concentrated in PIK3CA-altered patients. 67% patients concentrated in ctDNA subtype CSP. The proportion of patients in ctDNA subtype NF, ECF and CP is 23%, 13% and 6%, respectively. Kaplan–Meier curves showed that patients who received druggable ctDNA -guided late-line therapyalteration-guided treatment (DDAT) had significantly longer PFS than those who received physician-chosen therapy, with median PFS of 6.1 months versus 4.6 months (hazard ratio = 0.53, 95% CI: 0.34-0.85, Logrank P = 0.006). Conclusion: Multiple genetic alterations were important reasons for the failure of endocrine therapy for HR-positive and /HER2-negative metastatic breast cancerBC. Targeting these genes might restore the treatment sensitivity and benefit late-stagesurvival patients.